2006
DOI: 10.1186/1476-069x-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Occupational pesticide intoxications among farmers in Bolivia: a cross-sectional study

Abstract: Background: Pesticide use and its consequences are of concern in Bolivia due to an intensive and increasing use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
86
5
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 8 publications
17
86
5
4
Order By: Relevance
“…In this study, one-third of the farmers (33%) had received proper training on the handling of pesticides, which was higher than those reported in Jors et al study (25%) and Oesterlund et al's study (31%). 13,14 In this study, 40% of the farmers were unaware of the color-coding mark pertaining to pesticide level, which was exactly similar to the study result of Oesterlund et al 14 (40%). On the contrary, Jors et al 13 reported a higher number of farmers (71%) being unaware of the color codes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, one-third of the farmers (33%) had received proper training on the handling of pesticides, which was higher than those reported in Jors et al study (25%) and Oesterlund et al's study (31%). 13,14 In this study, 40% of the farmers were unaware of the color-coding mark pertaining to pesticide level, which was exactly similar to the study result of Oesterlund et al 14 (40%). On the contrary, Jors et al 13 reported a higher number of farmers (71%) being unaware of the color codes.…”
Section: Discussionsupporting
confidence: 76%
“…11,12 The symptoms of organophosphate and carbamate poisoning explored in this study were taken from two studies. 13,14 The symptoms explored were skin irritation, headache, respiratory difficulties, blurred vision, salivation, dizziness, extreme tiredness, muscular weakness, nausea, trembling hands, vomiting, and abdominal pain.…”
Section: Methodsmentioning
confidence: 99%
“…A survey conducted in 1996-1997 showed that 10% of produce exceeded the maximum residue limits for organophosphates (20). Acute poisoning from organophosphate exposure has not been reported, but occupational pesticide intoxication from organophosphate spraying has been described in Bolivian farmers (21).…”
Section: Discussionmentioning
confidence: 99%
“…Improper knowledge about the harmful chemicals influences to use these pesticides to prevent crop loss. A majority of farmers used pesticides, which either not registered for use in Bangladesh or restricted by WHO in underdeveloped countries (WHO, 2004;Jors et al, 2006;Shetty et al, 2011). Awareness about the occupational exposure among farmers was not adequate.…”
Section: Discussionmentioning
confidence: 99%